2018
DOI: 10.1002/anie.201810331
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling All‐Enzyme Hydrogels for Flow Biocatalysis

Abstract: Continuous flowbiocatalysis is an emerging field of industrial biotechnology that uses enzymes immobilized in flowchannels for the production of value-added chemicals.We describe the construction of self-assembling all-enzyme hydrogels that are comprised of two tetrameric enzymes.T he stereoselective dehydrogenase LbADH and the cofactorregenerating glucose 1-dehydrogenase GDH were genetically fused with aS pyTago rS pyCatcher domain, respectively,t o generate two complementary homo-tetrameric building blocks t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 56 publications
(3 reference statements)
7
81
0
Order By: Relevance
“…The in‐depth comparison of the enzymatic activities in solution revealed that the His‐LbADH variant showed a 13 % lower activity than a previously described LbADH variant with a 39‐amino acid SBP‐tag and a 30 % higher activity than an LbADH variant that contained the 113‐amino acid SpyCatcher domain for specific immobilization. The purified GDH‐His enzyme variant showed a more than threefold higher specific activity than a previously described GDH‐SBP variant ; however, the activity was still 20 % lower than that of a variant fused with the SpyTag (13‐amino acid) peptide . Although all enzyme activities found here are in the same order of magnitude, the slight changes nevertheless clearly emphasize that genetic fusion is often accompanied by changes in the specific activity.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The in‐depth comparison of the enzymatic activities in solution revealed that the His‐LbADH variant showed a 13 % lower activity than a previously described LbADH variant with a 39‐amino acid SBP‐tag and a 30 % higher activity than an LbADH variant that contained the 113‐amino acid SpyCatcher domain for specific immobilization. The purified GDH‐His enzyme variant showed a more than threefold higher specific activity than a previously described GDH‐SBP variant ; however, the activity was still 20 % lower than that of a variant fused with the SpyTag (13‐amino acid) peptide . Although all enzyme activities found here are in the same order of magnitude, the slight changes nevertheless clearly emphasize that genetic fusion is often accompanied by changes in the specific activity.…”
Section: Resultssupporting
confidence: 92%
“…The His‐tagged LbADH and GDH enzymes were cloned, heterologously overexpressed in E. coli and purified to homogeneity using IMAC as previously described . The purity of the enzymes was found to be > 95 %, as determined by SDS‐PAGE with subsequent Coomassie staining (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…[3a, 4] For the realization of such compartmentalized biocatalytic processes in continuous flow,t he fast and simple immobilization of enzymes inside the microstructured flow reactorsi sa ne ssential step to ensure efficients patials eparation of different reactions. [5] To enable the simple rapid prototyping of biocatalytic reaction modules for compartmentalized flow microreactors, we have recently established af abrication process using direct 3D printing of inexpensive biodegradable agarose-based hydrogel bioinks containingt hermostable enzymes( Figure 1). [6] 3D printing( also known as additive manufacturing) is af abrication process employing layer-by-layer deposition of materials to produce complex 3D structures with ah igh flexibility in designa nd minimal waste of material, [7] which has found applications ranging from the aerospace and constructioni ndustry to smart materials, medicine and biotechnology.…”
mentioning
confidence: 99%